Structural Dimensions of Pre-Service Teacher Preparation for Rural Multigrade Schooling - Ethem Gürhan; Makherus Sholeh (Journal of Asian Islamic Educational Management (JAIEM), 2026)
This study addresses a critical yet underexplored issue in rural education: the persistence of multi-grade schooling challenges the dominant competency-based model of teacher readiness by requiring teachers to operate in complex, structurally constrained environments. Despite a growing body of research on teacher preparation, existing studies largely conceptualize readiness as an individual competence, overlooking its structural and institutional dimensions. This study aims to reconceptualize teacher readiness by examining prospective primary school teachers’ preparedness for rural multi-grade schooling as a structurally mediated phenomenon. A qualitative descriptive research design was employed, drawing on written reflections of 70 final-year pre-service primary school teachers in Türkiye. The data were analyzed using thematic analysis to identify recurring patterns related to perceptions of professional readiness. The findings reveal that teacher readiness is shaped by the interaction of institutional and contextual structures, manifested through four interrelated dimensions: limited context-specific pedagogical preparation; expanded professional and administrative responsibilities; instructional fragmentation and time management constraints; and contextual limitations in rural schooling environments. Rather than representing isolated challenges, these dimensions collectively indicate that readiness is produced through systemic misalignments between teacher education programs and the realities of rural schooling. This study contributes to the literature by reconceptualizing teacher readiness as an institutional alignment rather than an individual competency deficit, and by highlighting the need for structurally responsive teacher education programs grounded in the complexities of rural and multi-grade school contexts.